ORGANIZATION OF CORRECTION PEDAGOGICAL WORK WITH CHILDREN WITH SEVERE SPEECH DEFECTS - Allambergenova, Mukhabbat Khasanbayevna; Sultanova, Jasmina Kuatbayevna (SCIENCE and SOCIETY, 2026)
The article analyzes innovative and comprehensive methods for overcoming dysarthria and alalia, which are severe pathological forms of speech ontogenesis and represent critical issues in modern special education and speech therapy. The primary objective of the study is to develop effective mechanisms for correcting speech disorders by integrating neurolinguistic, neuropsychological (Luria's LOK system), and pedagogical approaches. The paper provides a comparative analysis of the neuromotor nature of dysarthria and the cognitive-linguistic features of alalia, proposing models for hierarchical compensation and systematic language construction.
Keywords: dysarthria; alalia; severe speech defects; correctional methodology; conceptual metaphor; neurolinguistics; inclusive education